Estudo comparativo de dois tipos de cultivo: monocultivo (camarões) versus cultivo integrado (algas/camarões) - Freire, Alexandra Rafaela da Silva (2007)
The integrated culture of seaweed and aquatic animals is an ancient practice in Asian countries. The expansion of this practice to western countries is consequence of the recognition of this system as a sustainable alternative that allows economical diversification and mitigation of environmental impacts generated by effluents of aquaculture. This study evaluated the growth of the seaweed Gracilaria caudata and of the shrimp Litopenaeus vannamei in monoculture (shrimps) and integrated culture (shrimps and algae) systems, and accessed the effect of the seaweed in the water quality. There were two treatments in the experiment: monoculture (shrimps) and integrated culture (shrimps/ algae). The organisms were cultured in 6 aquaria (10L) filled with seawater (35.0±0.0 PSU and 28.1±0.4°C) for 28 days. The nutrients of water (PO43-, NH4+, NO2-, NO3- and DIN), the biomass and the relative growth rate (RGR, % day-1) of seaweed and shrimps were measured weekly. The parameters pH, temperature, salinity and dissolved oxygen were measured daily. The concentration of NH4+ in integrated culture (62.8±25.2µM) was lower (Mann-Whitney p<0.001) than in monoculture (85.6±24.3µM). The mean of PO4- in monoculture (10.4±4.6µM) was markedly higher (Mann-Whitney; p=0.024) than that in integrated culture (8.7±4.1µM). The level of dissolved oxygen in integrated culture (6.0±0.6mg/L) was higher (t-Student; P=0.014) than that in shrimp monoculture (5.8±0.6mg/L). The mean values of the parameters pH, NO2-, NO3- and DIN were 7.5±0.2, 10.1±12.2µM, 24.5±3.2µM and 120.17±30.76µM in monoculture, and 7.5±0.2, 10.5±13.2µM, 27.4±3.5µM and 100.76±49.59µM in integrated culture. There were not differences in these parameters between treatments. The biomass and RGR of seaweed reached 15.0±1.9g and 7.4±2.8% day-1 at the end of the experiment. The performance of shrimp was favorable in monoculture (1.5±0.8g; 5.7±1.6% dia-1) and in integrated culture (1.5±0.7g; 5.2±1.2% dia-1), and the rate of survival was 100% in both treatments. The tolerance and favorable performance of Gracilaria caudata suggest that this seaweed might be integrated into shrimp (Litopenaeus vannamei) culture systems